Konsep Dasar Ilmu Menurut Mohammad Hatta ditinjau dari segi Ontologi, Epistemologi, dan Aksiologi - Mutiara Vidazeya; Yeni Karneli; Puji Gusri Handayani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to examine the basic concept of science according to Mohammad Hatta from the perspective of the philosophy of science, which includes the dimensions of ontology, epistemology, and axiology. As one of the nation’s figures and influential Muslim thinkers, Mohammad Hatta offered a philosophical view that places science as an integral part of human spiritual, social, and moral life. Through a literature study approach, this study collects and analyzes various scientific sources in the form of books, journal articles, and documentation of Hatta’s thoughts that are relevant to the discussion of Islamic science and education. Thematic analysis is used to identify the main patterns of thought regarding the nature of science, the process of acquiring knowledge, and the value and purpose of its use in community life. Hatta views science as rooted in the order of God’s creation and objective reality that can be understood through reason. From an epistemological perspective, Hatta emphasizes the combination of reason, empirical experience, and moral values ​​as the basis for the process of acquiring knowledge, while rejecting the separation between science and religion.